Evaluation of the activity of disinfectants against coliform bacteria group strains isolated from a sewage treatment plant (ETE-Ipanema) - Silveira, Anelise Beneduzi da; Bechtlufft, Marcelo de Paiva; Van Der Sand, Sueli Teresinha; Corção, Gertrudes (Acta Scientiae Veterinariae, 2018)
Municipal wastewater usually presents pathogenic enteric bacteria, viruses and intestinal parasites. Primary, secondary and tertiary wastewater treatment eliminates 90-99.9% of these microorganisms and if a more efficient reduction of microorganisms is needed, disinfection with chemical compounds must be done. The extraordinary genetic variability of bacteria gives them adaptation ability against theses chemical agents, which indiscriminate use brings about serious health problems. In this study, chemical agents commonly used in disinfection procedures like chlorhexidine gluconate, sodium hypochlorite and quaternary ammonium compounds were investigated for their activity against bacteria from the coliform group, isolated from a sewage treatment plant, using the macrodilution method. It was observed that the addition of organic matter interferes in sensitivity levels and also that the lower the concentration and the exposure time, the higher the resistance. Sodium hypochlorite was the most effective against the coliforms, once inhibited their growth in every exposure time and at every disinfectant concentration used . Quaternary ammonium compounds and chlorhexidine gluconate were also effective, although a higher percentage of resistance was observed for both.